2003
DOI: 10.1051/vetres:2002062
|View full text |Cite
|
Sign up to set email alerts
|

Sequence analysis demonstrates the conservation of fimH and variability of fimA throughout Avian Pathogenic Escherichia coli (APEC)

Abstract: -In this study we sequenced and analysed the fimH and fimA genes of 24 avian pathogenic Escherichia coli (APEC) isolates, in order to investigate their possible conserved nature. Additional parameters (serotype, presence of aerobactin receptor, expression of F1 pili and virulence for chickens) were investigated to look for correlations with the obtained sequences. The sequence analysis demonstrated that FimH is highly conserved among all investigated APEC strains (> 99% homology), whereas the major subunit Fim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…APEC strain CH2 (O78) was isolated from an infected chicken and is virulent in experimentally infected chickens (P. van Empel, personal communication). This strain contains the fimH gene, as confirmed using a polymerase chain reaction (PCR) assay, and is able to express type 1 fimbriae, as shown by haemagglutination, using protocols described in Vandemaele et al (2003a). APEC 1 (Vandemaele et al , 2003b) is a virulent serotype O45 strain containing the FimH adhesin.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…APEC strain CH2 (O78) was isolated from an infected chicken and is virulent in experimentally infected chickens (P. van Empel, personal communication). This strain contains the fimH gene, as confirmed using a polymerase chain reaction (PCR) assay, and is able to express type 1 fimbriae, as shown by haemagglutination, using protocols described in Vandemaele et al (2003a). APEC 1 (Vandemaele et al , 2003b) is a virulent serotype O45 strain containing the FimH adhesin.…”
Section: Methodsmentioning
confidence: 99%
“…This strain has been transformed with plasmid pEGFP (Clonetech; BD Biosciences, NJ, USA), containing the gene for EGFP. APEC 54 (Vandemaele et al , 2003a) is a virulent serotype O2 strain, also containing the FimH adhesin. Plasmid pPCR SCRIPT AMP SK (Stratagene, La Jola, CA, USA) was used for direct cloning of blunt-end PCR products and sequencing, and plasmid pET22b (Novagen, Madison, WI, USA) was used as an expression vector.…”
Section: Methodsmentioning
confidence: 99%
“…Strain CH4 was a virulent O2 papG II ' strain ( Van den Bosch et al , 1993). All strains were papG II ' , as verified by polymerase chain reaction (PCR) and sequencing, and expressed P fimbriae, as shown by mannose-resistant haemagglutination of human blood group A erythrocytes using protocols described by Vandemaele et al (2003a). Plasmid pPCR SCRIPT AMP SK (Stratagene, La Jola, California, USA) was used for direct cloning of blunt-end PCR products and sequencing, and plasmid pET22b (Novagen, Madison, Wisconsin, USA) was used as an expression vector.…”
Section: Methodsmentioning
confidence: 99%
“…The expression of this gene is responsible for fimbriae adhesion to intestinal epithelium and colonization of the mucosa [41]. Previous studies indicated the high conservation of this gene in pathogenic E. coli from avian origin (APEC) (>99% homology), which is a subgroup of the extra-intestinal pathogenic E. coli pathotype (ExPEC) [42]. Additionally, the presence of the cvaC gene (which codifies a toxin) in the majority of the isolates tested (23 out of 26) also suggests the presence of E. coli from birds in these water spots.…”
Section: E Flores Et Almentioning
confidence: 99%